Recycling of paper, cardboard and its PFAS in Norway - Håkon A. Langberg; Hans Peter H. Arp; Gabriela Castro; Alexandros G. Asimakopoulos; Heidi Knutsen (Journal of Hazardous Materials Letters)
Per- and polyfluoroalkyl substances (PFAS) have been used in paper products since the 1960s. PFAS emissions during the life cycle of these products have been substantial sources of these substances to the environment. Here, a total of 37 PFAS were analysed in 13 paper products sampled in 2021, for which some were made of virgin paper and others recycled paper, including food contact materials (FCM), packaging, and a notebook. In addition, different fractions of the recycling process of corrugated paper and board were sampled at a Norwegian cardboard recycling plant and analysed for the same PFAS, to get an overview of PFAS in the recycling stream of these materials in Norway. PFAS were found in recycled paper and board, indicating PFAS can be a non-intentionally added substance (NIAS) in recycled paper products. Sum of targeted PFAS detected in paper products (including products made of virgin and recycled materials) ranged between 0.4 and 971 µg kg−1, dominated by SAmPAP diester and 6:2 FTS (0–62% and 0–98%, respectively). The sum of targeted PFAS in returned corrugated paper and board in Norway is at least 32 kg per year (6 mg per capita per year). Recycling is important to ensure sustainability. As part of the broad PFAS restriction in Europe, PFAS are to be restricted in paper and board materials. Thus, lower levels of PFAS entering the recycling stream are expected in the future. Monitoring is necessary to assess reductions of PFAS in the paper waste stream due to PFAS regulations in Europe.